Student Project A comparison of natural & synthetic rooting hormones for vegetative propagation using Saxagothaea conspicua Lindl. - Isabel Cayon-Fernandez (Sibbaldia, 2020)
This paper examines the effects of using natural and synthetic rooting hormones for cuttings propagation. The study used Saxegothaea conspicua Lindl, a Near Threatened conifer native to Chile and Argentina. A trial was set on 80 semi-ripe cuttings of S. conspicua applying both synthetic (IBA) and natural hormones derived from willow and lentils. This study evaluates and measures the rooting success of using different types of hormones at the end of the trial (such as development of roots, length, etc). It also aims to examine the level and type of auxins found in the lentil and willow rooting solution, if present. After evaluation of results of the present trial and the wider literature, this paper discusses the potential use of this type of natural hormones in future.